Mutace genu EGFR u pacientů s pokročilým NSCLC - Fiala, O; Pešek, M; Fínek, J; Brůha, F; Bortlíček, Z; Krejčí, J; Benešová, L; Minárik, M (Klinicka onkologie, 2012)
BACKGROUND: Molecular targeted therapy based on tyrosine kinase inhibitors, directed at the epidermal growth factor receptor (EGFR) is one of novel options for management of NSCLC. EGFR gene mutations, exon 19 deletions and exon 21 point mutations (L858R) are good predictors of response to EGFR-TKI treatment. The aim of this study was to assess the incidence of EGFR mutations in a large cohort of Europeans with advanced NSCLC and subsequently to evaluate their impact on the effect of EGFR-TKI treatment. PATIENTS AND METHODS: In total, 613 patients with advanced stage NSCLC (IIIB, IV) were genetically tested. The effect of treatment was evaluated in 410 patients treated with EGFR-TKI. Survival was evaluated using Kaplan-Meier method, and statistical comparison was performed using log-rank test. RESULTS: EGFR mutations were detected in 73 (11.9%) patients. Exon 19 deletions were detected in 49 patients, exon 21 point mutations (L858R) were detected in 22 patients, and both mutation types were detected in 2 patients. An increased incidence of EGFR mutations among patients with adenocarcinoma (14.9% vs 7.8%, p = 0.008), women (20.2% vs 7.1%, p < 0.001) and nonsmokers (29.9% vs 7.0%, p < 0.001) was demonstrated. Sixty patients with EGFR mutation and 350 patients with wild-type EGFR were treated with EGFR-TKI. Median PFS in patients harboring EGFR mutation was 7.2 vs 2.0 months in patients harboring wild-type EGFR (p < 0.001), median OS in patients harboring EGFR mutation was 14.5 vs 7.5 months in patients harboring wild-type EGFR (p = 0.019). CONCLUSION: The incidence of EGFR mutations in the studied population, their increased incidence among patients with adenocarcinoma, women and non-smokers correlated with data previously published. Results of survival analysis in patients treated with EGFR-TKI confirmed high potential of EGFR mutations to predict good effect of the EGFR-TKI treatment. Genetic testing in patients with NSCLC should be a standard part of diagnostic procedures
Keywords: Quinazolines; Protein Kinase Inhibitors; gefitinib; Protein-Tyrosine Kinases; Middle Aged; mužské pohlaví; Gefitinib; ErbB Receptors; nádory plic; mutace; míra přežití; Antineoplastic Agents; chinazoliny; ženské pohlaví; nemalobuněčný karcinom plic; protinádorové látky; Mutation; Humans; Survival Rate; erlotinib; Carcinoma, Non-Small-Cell Lung; erbB receptory; Erlotinib Hydrochloride; lidé středního věku; tyrosinkinasy; inhibitory proteinkinas; Female; Lung Neoplasms; lidé; Male